Graphene oxide promotes soybean growth by reshaping the rhizosphere microbiome and enhancing soil fertility - Qiao, Jun; Shen, Lijia; Liu, Jiahao; Sun, Jiao; Dai, Zijun; Hu, Jianwen; Du, Changjian; Yang, JiaSheng; Li, Jingwei; Zhao, Jianguo; Chen, Xiaokang (Frontiers in Plant Science, 2025)
Soybean (Glycine max L.) one of the world’s most important crops that is prized for its high protein and lipid content. As a prominent member of the carbon nanomaterial family, graphene oxide (GO) exhibits remarkable fertilizer adsorption and slow-release capabilities owing to its high specific surface area and abundant oxygen-containing functional groups, demonstrating broad application prospects in agricultural production. However, its potential role in regulating soybean growth and modulating the rhizosphere microbiome remains poorly understood. To elucidate the mechanism by which GO modulates soybean growth, we investigated eight cultivars (SN24, CD5, 7534, 15GI-16, ZH75, G135, L2012-7, and CD13) with a 30 mg/L GO treatment. The results demonstrate that GO application significantly enhanced key agronomic traits, increasing plant height by 7.17–51.05%, stem diameter by 12.39–63.34%, and the number of root nodules by 33.33–328.57%, along with increase in root biomass. Rhizosphere microbiome analysis revealed that GO restructured microbial communities in L2012–7 and significantly increased bacterial and fungal abundance or diversity based on operational taxonomic unit (OTU) levels (p < 0.05). Taxonomic profiling identified GO-enriched beneficial genera (Sinorhizobium, Sphingomonas and Trichoderma), with LEfSe and Random Forest analyses confirming that Sinorhizobium is a keystone taxon. Mechanistically, Sinorhizobium fredii (Sf01) was successfully isolated and identified from soybean rhizosphere soil, which was shown to promote soybean growth. Treatment with 5, 30, and 50 mg/L GO promoted the colony growth of S. fredii (Sf01) by 40.2%, 42.9%, and 55.5%, respectively, whereas 100 mg/L GO inhibited its growth compared to the control. Furthermore, soil nutrient analysis demonstrated that GO significantly enhanced the contents of soil organic matter, total nitrogen, available potassium, available phosphorus, ammonium nitrogen, and humic acid in soybean rhizosphere soil. Our experimental results demonstrate that GO reshapes the soybean rhizosphere microbial community, which in turn enriches keystone beneficial microbes S. fredii (Sf01) and enhances soil fertility retention capacity. This cascade of effects collectively promotes soybean plant growth, offering a nano-enabled strategy to reduce reliance on synthetic fertilizers.